Jamnagar Petrochemical Complex, Gujarat - Reliance Industries Limited (2023)
Jamnagar refinery was built in 1999 by Shri Mukesh Ambani fulfilling his father, Shri Dhirubhai Ambani's dream of an oil and petrochemical refinery in India.